دور التحقيق الجبائي المعمق في تفعيل الحوكمة الضريبية لمكافحة التهرب الضريبي دراسة ميدانية بالمديرية الفرعية للرقابة الجبائية بسطيف - راشــدي, أمــــــين (University of Eloued جامعة الوادي, 2017)
هدفت هذه الدراسة إلى توضيح العلاقة بين المراجعة الجبائية والحوكمة الضريبية وأثرها على الحصيلة الضريبية، إذ تعد المراجعة الجبائية وسيلة وقائية وأداة رقابية فعالة، الهدف منها ضمان احترام المكلف بالضريبة للقوانين المعمول بها خاصة في ظل النظام الضريبي التصريحي المعتمد. وقد تم التوصل من خلال الجانبين النظري والتطبيقي إلى أن الحوكمة الضريبية ممثلة في المراجعة الجبائية لها دور مهم جدا في الحفاظ واسترجاع جزء هام من الحصيلة الضريبية وقد تم إظهار ذلك من خلال دراسة حالة التحقيق المعمق في مجمل الوضعية الجبائية (VASFE) بمديرية الضرائب لولاية سطيف؛ وفي الأخير تم التوصل إلى أن المراجعة الجبائية مهمة جدا في تفعيل الحوكمة الضريبية ومكافحة التهرب الضريبي، والمساهمة بشكل كبير في زيادة التحصيل الضريبي. Abstract: This study aimed to clarify the relationship between the fiscal audit and the tax governance and their impact on the fiscal revenue. In fact, the fiscal audit is a preventive and effective control tool for respecting the tax laws, especially the declarative fiscal system. Based on theoretical and practical parts , it has been shown that the fiscal governance represented by the fiscal audit has a very important role in the preservation and recovery of significant tax revenue ; This result had been verified through the study of the in-depth investigation case in the overall fiscal position in the Setif taxes directorate. Finally, the study had shown that the fiscal audit is an important instrument that is used to improve the fiscal governance, overcome the fiscal evasion and increase the fiscal revenue
The role of the fiscal audit in depth for activating the tax governance to face the fiscal evasion: practical study of the fiscal control sub-directorate of Sétif
مجلة رؤى المجلد السابع العدد 12
Keywords: الحوكمة الضريبية، المراجعة الجبائية، التحصيل الضريبي.: fiscal governance, fiscal audit, fiscal revenue. (JEL) Classification :H26